Sala de recursos multifuncionais: um estudo de caso - Oliveira, Cassia Carolina Braz de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The current Education Policy establishes the Specialized Educational Services based on the implementation of Multifunctional Resource Classes (MRC), Type I and Type II. Many cities adopted the MRC as their main specialized education system, resulting in an increased number of enrollments of students with special needs in regular classes. In this context, this research was conducted to address the growing need to study the MRC; considering the complexity and amplitude of the theme, 14 questions were raised with the objective of studying the MRC as the locus of the Specialized Educational Services. The main objective of this research was to describe and analyze, using a set of questions proposed by the literature, the services offered in a MRC of a city in the state of São Paulo. The specific objectives were represented by the 14 questions, among which are questions that try to identify, analyze, describe and verify various aspects of the special education services such as the reasons that lead the city to implement MRC in its schools, the academic background of the specialist teacher, the school-family relationship and the contact between the specialist and the regular education teacher; and also specific questions about the strategies and resources used for teaching in the MRC. The research was based upon a Case Study, which is characterized by the definition based on pre-established criteria of the research unity. The research locus was an elementary school of the municipal education system of a city in the state of São Paulo. The instruments used for the data collection were structured interviews, observation schedules, the accessibility protocol and the Assistive Technology questionnaire. The participants were the local Special Education coordinating body, the specialist teacher, the regular teacher and the school board. Triangulation was used to analyze the data which was then organized in chapters according to the proposed objective. The results showed that the use of the 14 questions allowed for an extensive study of the MRC; they also showed, though, that it would be possible to elaborate new questions regarding, for instance, the socioeconomic indicators of the studied region, considering they had a considerable degree of influence over the study. The results also revealed a need to enunciate specific questions about the locus which will be studied, considering all the regional, cultural and economic differences that exist between different education systems. A necessity to dedicate some efforts towards preparing the special education teacher on how to correctly and efficiently handle the Assistive Technology, to define the resources and strategies backed by theoretical support, to strengthen the communication between the regular and the specialist teacher and between the school and the student’s family, and to enhance the accessibility policies were also observed by analyzing the results.

A Política de Educação atual estabelece o Atendimento Educacional Especializado (AEE) centrado na implementação de Salas de Recursos Multifuncionais (SRM), Tipo I e Tipo II. A definição das SRM como modelo central de investimentos foi consolidando-se em diversos municípios, resultando no aumento de matrículas de alunos públicos-alvo da Educação Especial nas escolas regulares. Considerando a complexidade e a necessidade de estudos sobre as SRM, visto sua amplitude, foram definidas 14 questões que têm como objetivo possibilitar um estudo da SRM como lócus do AEE. O objetivo geral desta pesquisa foi: descrever e analisar, a partir de um conjunto de questões propostas pela literatura, os serviços oferecidos em uma SRM de um município do interior paulista. Os objetivos específicos propostos foram 14 questões que buscam identificar, analisar, descrever e verificar diversos aspectos presentes, como o motivo da implementação das SRM no município, a formação do professor especialista, relação escola-família, contato entre o professor especialista e o professor da classe regular e questões específicas sobre a prática, estratégias de ensino e recursos utilizados nos atendimentos que ocorrem na SRM. A pesquisa configurou-se em um Estudo de Caso, que tem como característica a definição baseada em critérios preestabelecidos da unidade de pesquisa. O local da pesquisa, foi uma escola de ensino fundamental da rede de ensino municipal de uma cidade do interior do estado de São Paulo. Como instrumentos de coleta de dados, foram utilizados roteiros de entrevista, roteiros de observação, o protocolo de acessibilidade e o questionário de Tecnologia Assistiva. Os participantes foram as coordenadoras de Educação Especial do município, a professora especialista, professora regular e a coordenação da escola. Os dados foram analisados com base na triangulação de dados e apresentados em capítulos de acordo com o objetivo proposto. Os resultados revelaram que a utilização das 14 questões possibilitou um estudo amplo da SRM; também mostraram, porém, que seria possível a articulação de novas questões como, por exemplo, sobre a variável socioeconômica da região estudada, visto que esta estava presente em diversos pontos do estudo. Os resultados também indicaram a necessidade do levantamento de perguntas direcionadas especificamente para o lócus que será estudado, considerando as diferenças regionais, culturais e econômicas das diferentes redes de ensino. Dentre os resultados encontrados estavam a necessidade de investimentos na formação do professor especialista para a utilização de Tecnologia Assistiva, da definição de recursos e estratégias com suporte teórico, de fortalecer o contato entre o professor especialista e o professor regular e entre a escola e a família e da ampliação de políticas de acessibilidade.
Multifunctional resource class: a case study
Keywords: Special education; Specialized educational services; Multifunctional resource class; Assistive technology; Educação especial; Atendimento educacional especializado; Sala de recursos multifuncionais; Estudo de caso; Tecnologia assistiva